2015
DOI: 10.1080/17512786.2015.1017400
|View full text |Cite
|
Sign up to set email alerts
|

Where do journalists go after newsroom job cuts?

Abstract: This article explores the aftermath of job loss for a sample of Australian journalists who were made redundant in 2012, a year of dramatic press industry restructuring. It reports the findings of a pilot study of 95 redundant journalists, undertaken as part of the New Beats project, a five-year longitudinal study of job loss in journalism. Three related questions drive the analysis: Where do journalists go after job cuts? How do they make sense of job loss? What happens to professional identity? In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
(15 reference statements)
2
47
0
4
Order By: Relevance
“…This second strategy had a disproportionate effect on older journalists, meaning that newsrooms also lost significant expertise and knowledge. This mirrors the work of O'Donnell et al (2015) in the Australian context, which found that redundancy processes led to a loss of journalistic corporate memory from newsrooms. Given that this paper addresses the Australian context, this study is relevant and timely.…”
Section: Literature Reviewsupporting
confidence: 66%
See 2 more Smart Citations
“…This second strategy had a disproportionate effect on older journalists, meaning that newsrooms also lost significant expertise and knowledge. This mirrors the work of O'Donnell et al (2015) in the Australian context, which found that redundancy processes led to a loss of journalistic corporate memory from newsrooms. Given that this paper addresses the Australian context, this study is relevant and timely.…”
Section: Literature Reviewsupporting
confidence: 66%
“…The survey rationale and design drew directly on insights gained from an exploratory pilot study undertaken in 2013 (see O'Donnell et al, 2015). Three insights were particularly helpful.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of propaganda is not a recent invention, but it is ever-present throughout history (Bazerman, 2016). However, during the last 10-15 years we have witnessed enormous changes: an ever-faster pace of news dissemination (John and Silberstein-Loeb, 2015), a massive volume of digital information, a growing mistrust in traditional media (Nicolaou and Giles, 2017), a worsening of journalists' work conditions (O'Donnell et al, 2016) and a spectacular rise of information on the Internet. According to a scientific report by the Joint Research Center of the European Commission (Martens et al, 2018), two out of three Internet users prefer to access the news through platforms based on algorithms, such as search engines, news aggregators and especially so-cial networks.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, which will serve as a national example in this article, the expansion of commercial media, media management, and the PR industry (Garsten et al 2015) in recent decades has led to fewer barriers between politics, media and PR in the workforce. In Sweden, but also elsewhere (O'Donnell et al 2016;Macnamara 2016, 133), many unemployed or freelancing journalists, as well as politicians, are increasingly finding the PR business a lucrative option and therefore migrate to the commercial sector (Tyllström 2010), but the traffic might also go in the other direction (Allern 2011;Garsten et al 2015). A growing number of professionals with 'ex'-prefixes are becoming important agents of convergence culture, be they ex-journalists, now active in PR; ex-PR practitioners, now active in politics; or 'both/and' practitioners who are active in several fields simultaneously.…”
Section: Introductionmentioning
confidence: 99%